Persepsi Mahasiswa Tentang Fasilitas Belajar Pada Prestasi Belajar - Widy Nurwiandani; Bhisma Murti; Hari Wujoso (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Educational success will be achieved when the resulting achievement in the educational process issatisfactory. The factors that influence an individual learning consists of three kinds, namely internal factors and,external factors, and factor approach to learning. Purpose of this research was to analyze the effect learning facilities on student learning achievement.Methods: This research used the quantitative observational with th cross-sectional design. Population in this research are students of third level Midwifery Academy Estu Utomo and Yappi Sragen Utomo and students. Sampleof 40 students with a simple random sampling technique. Means of collecting data using questionnaires. Analysisof data used multiple linear regression with SPSS.Results: The results showed that there are positive and statistically significant effect between learning facilities onstudent achievement. (b1 =0.55CI=95%0.24to0.86, p =0.001).Conclusion: This study concludes that there are effects of students perseption about learning facilities on academic achivemend.Keywords: learning facilities and learning student achievement